2011
DOI: 10.1016/j.ydbio.2011.03.010
|View full text |Cite|
|
Sign up to set email alerts
|

FGF8 signaling is chemotactic for cardiac neural crest cells

Abstract: SUMMARY Cardiac neural crest cells migrate into the pharyngeal arches where they support development of the pharyngeal arch arteries. The pharyngeal endoderm and ectoderm both express high levels of FGF8. We hypothesized that FGF8 is chemotactic for cardiac crest cells. To begin testing this hypothesis, cardiac crest was explanted for migration assays under various conditions. Cardiac neural crest cells migrated more in response to FGF8. Single cell tracing indicated that this was not due to proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 47 publications
2
92
1
Order By: Relevance
“…In this report, we have investigated whether FBLN1, a known extracellular glycoprotein (7) as well as an intracellular integrin ␤1-binding protein (22), and FGF8, a known effector of NCC migration (21), associate with each other biochemically and have synergistic effects on embryonic development or survival. Herein, we show for the first time that FBLN1 binds with high affinity to FGF8 and protects it from enzymatic degradation by ADAM17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we have investigated whether FBLN1, a known extracellular glycoprotein (7) as well as an intracellular integrin ␤1-binding protein (22), and FGF8, a known effector of NCC migration (21), associate with each other biochemically and have synergistic effects on embryonic development or survival. Herein, we show for the first time that FBLN1 binds with high affinity to FGF8 and protects it from enzymatic degradation by ADAM17.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that inhibition of FGF8 signaling in the absence of NCC ablation causes under-proliferation of secondary heart field cells, resulting in a shortened outflow tract (18). Additionally, it has been shown that FGF8 acts as a chemotactic and chemokinetic signal for cardiac neural crest cells both in vitro and in vivo (21). Thus, precise levels of FGF8 signaling seem critical for normal outflow tract development and morphogenesis.…”
Section: Fibulin-1 (Fbln1)mentioning
confidence: 99%
“…In the mouse, FGF2 and FGF8 have been found to control NC migration towards the branchial arches (Kubota and Ito, 2000;Trokovic et al, 2005), while in chick an equivalent role has been described for VEGFA . Also in chick, cardiac NC cells seem to rely on FGF8 and semaphorin 3C (here acting as a positive cue) to reach the heart (Lepore et al, 2006;Sato et al, 2011). Finally, data from chick and mouse have demonstrated that GDNF controls enteric NC rostrocaudal progression along the gut to form the enteric nervous system (Sasselli et al, 2012;Young et al, 2001).…”
Section: Neural Crest Guidancementioning
confidence: 99%
“…Because in other tissues Fgfs act as chemoattractive signals (Sutherland et al, 1996;Sato et al, 2011;Kadam et al, 2012), we considered the possibility that Fgfs also have a more direct role in lateral line cell migration. We analysed the expression of Fgf signalling components and found that after the fusion between the SPCs and primordium, fgf3 and fgf10 are expressed in the leading zone, and fgfr1 in the trailing zone, as previously reported ( , 2008).…”
Section: Fgf Signalling Attracts Spcs Towards the Main Primordiummentioning
confidence: 99%